Pengendalian Kualitas Produk Part Grip Model D55L Dengan Pendekatan Six Sigma Di PT.Z - Aliyya Rizqi Amani; Wahyudin, Wahyudin (Fakultas Teknik Universitas Tulang Bawang, 2024)
The existence of the Industrial Revolution 4.0, progress, and developments over time are starting to change the way consumers view a company. PT.Z uses this to retain and attract consumers by controlling the quality of its products. The aim of the research was to identify product quality related to the causes of defects in the D55L grip part as the product that experienced the most defects in the 3 month period of observation activities and to obtain suggestions for improvements in order to minimize variance to zero defects. The method used starts with conducting a study until data collection and processing are carried out using the Six Sigma approach. So the number of products was 75,242 with 5 types of product defects totaling 863 defects, DPMO 2,289, sigma value of 4.34, and yield 4-σ (Sigma 4) 99.771% which is equivalent to the industry in the USA, and the main causal factors were found which were grouped into Man, Machine, Method, and Material. With the existence of Six Sigma, recommendations for improvements were obtained for the company by meeting the target of 0.01% and it was concluded that quality control at PT.Z is under control. Keywords: Defect, Grip, Product, Quality, Six Sigma